Postpartum contraception: optimal choice - Bakhareva I.V (LCC «Medicine-Inform», 2020)
I.V. Bakhareva Pirogov Russian National Research Medical University, Moscow, Russian Federation Family planning and contraception after childbirth are important medical and social issues. Reproductive health and full preconception planning (which ensure uncomplicated course of the pregnancy), the birth of healthy children, and prevention of unintended pregnancy will be provided by addressing these issues. The major goals of postpartum family planning are optimal time between the end of the first pregnancy and the conception of the next (at least 2-3 years) as well as the reduction of maternal risks, perinatal and infant morbidity and mortality, and the rate of medical abortions. All these aspects require the choice of optimal postpartum contraception for the couple. This paper discusses current views on the methods of postpartum contraception, both traditional (i.e., lactational amenorrhea, barrier contraceptives, calendar method) and contemporary (hormonal methods). Despite being relatively conservative about postpartum contraception in view of the potential effects  of hormonal agents on the child during breastfeeding, modern highly effective methods of long-acting reversible contraception immediately after childbirth (mainly intrauterine devices and implants) are being actively sought worldwide. The choice of optimal method of contraception during breastfeeding, antenatal and postpartum consultation will help decide on the potential risk of unintended pregnancy, contraception method, and the risk of breastfeeding problems. Keywords: contraception, hormonal contraceptives, postpartum period, breastfeeding. For citation: Bakhareva I.V. Postpartum contraception: optimal choice. Russian Journal of Woman and Child Health. 2020;3(1):-38. DOI: 10.32364/2618-8430-2020-3-1-31-38.